2022
DOI: 10.1111/all.15295
|View full text |Cite
|
Sign up to set email alerts
|

Allergen immunotherapy for asthma prevention: A systematic review and meta‐analysis of randomized and non‐randomized controlled studies

Abstract: Background: Allergen immunotherapy (AIT) is a disease-modifying treatment for IgEmediated diseases. Randomized controlled trials (RCTs) support AIT's potential role in asthma prevention but evidence from non-randomized studies of interventions (NRSI) and longitudinal observational studies has been poorly addressed. Therefore, we aimed to conduct a systematic review and meta-analysis to assess clinical data from all study types to evaluate quantitatively the preventive role of AIT in asthma onset. Methods:We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 48 publications
0
36
1
2
Order By: Relevance
“…A recent meta-analysis suggested a preventive effect of allergen immunotherapy in asthma development, confirming the association found in previous studies. 2 The application of AIT in inhalant allergies is recommended by international medical organizations both for its efficacy and safety. 3–7 While AIT is highly appraised, a discussion continues concerning further optimization of both its efficacy and safety, including its immediate and remote effects.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis suggested a preventive effect of allergen immunotherapy in asthma development, confirming the association found in previous studies. 2 The application of AIT in inhalant allergies is recommended by international medical organizations both for its efficacy and safety. 3–7 While AIT is highly appraised, a discussion continues concerning further optimization of both its efficacy and safety, including its immediate and remote effects.…”
Section: Introductionmentioning
confidence: 99%
“…AR had been identified to be a crucial risk factor of asthma in many studies [ 34 , 35 ]. There was also evidence suggesting that early intervention of AR such as allergen immunotherapy precluded the development of asthma [ 36 , 37 , 38 , 39 ]. Raised awareness of asthma will push AR patients to take more actions to avoid developing asthma.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that AITs may be effective for allergic diseases because of the conversion of allergen-specific effector Th2 cells into tolerance-inducing Tr1 cells by repeated allergen administrations. Indeed, many studies [reviewed in ( 10 , 87 )] have demonstrated that AIT can be effective for various allergic diseases, and the frequency of allergen-specific Tr1 cells was correlated with the decrease in clinical scores ( 79 82 ). Taken together, these studies suggested that Tr1 cells play a critical role in the induction of immunotolerance to allergens in humans.…”
Section: Clinical Relevance Of Tr1 Cells In Allergy and Aitmentioning
confidence: 99%